Degenerate Nevanlinna-Pick problem - Dyukarev, Yu. M. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
A general solution of the degenerate Nevanlinna-Pick problem is described in terms of fractional-linear transformations. A resolvent matrix of the problem is obtained in the form of a J-expanding matrix of full rank.